2021
DOI: 10.12659/ajcr.927757
|View full text |Cite
|
Sign up to set email alerts
|

Primary BRAF Mutant Melanoma of the Lung Treated with Immunotherapy and Pulmonary Bilobectomy: A Case Report

Abstract: Patient: Female, 59-year-old Final Diagnosis: Melanoma malignant • mucosal melanoma Symptoms: Cough • hemoptysis • weigh loss Medication: — Clinical Procedure: Lymph node excision • pulmonary bilobectomy Specialty: Oncology • Surgery Objective: Rare disease Background: Primary melanoma of the lung is a rare tumor that represents 0.01% of primary lung tumors, with only 40 cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Dabrafenib and trametinib are commonly used to treat patients with BRAF V600E mutated malignant melanoma of the skin [7]. Two out of three patients with BRAF V600E mutated PMML were treated with this combination therapy [3,5,6]. In our case, the patient showed disease control for approximately 2 years, indicating that this combination treatment was effective for BRAF V600E mutated PMML.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Dabrafenib and trametinib are commonly used to treat patients with BRAF V600E mutated malignant melanoma of the skin [7]. Two out of three patients with BRAF V600E mutated PMML were treated with this combination therapy [3,5,6]. In our case, the patient showed disease control for approximately 2 years, indicating that this combination treatment was effective for BRAF V600E mutated PMML.…”
Section: Discussionmentioning
confidence: 57%
“…However, the incidence of genetic alterations in PMML remains unclear because of its rarity. To date, there have been only 13 reports of genetic analyses in PMML tumors, in which only 3 tumors (23%) have been reported to be BRAF-mutated [3,5,6].…”
Section: Discussionmentioning
confidence: 99%
“…The concurrent use of ipilimumab and nivolumab has manageable safety profiles and produced clinical data different from published monotherapy activity, achieving rapid and profound tumor regression ( 18 ). A study has also demonstrated the efficacy of post-operative surgery and the ability of anti-PD1 (pembrolizumab) to shrink mucosal melanoma to a size that allows for resection ( 19 ). The size of PMML decreased from 54 mm × 50 mm to 16 mm × 10 mm, a size that could be surgically removed.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of patients have been reported with a better prognosis. Bernal et al 15 reported a case of unresectable PMML with clinical stage IIIB (T4N2M0) disease. The patient obtained a partial response to pembrolizumab and underwent radical surgery.…”
Section: Discussionmentioning
confidence: 99%